The Navruz holiday or the day of the vernal equinox in the history and culture of the peoples of the East - T.T.Khalimov (Genius Publishing Group, 2022)
This article provides information about the history of Navruz (the day of the vernal equinox) and its role in the culture of different peoples. The article also includes information about the beginning of the new year in the history of the peoples of the East, the culture of agriculture and a number of rituals related to them
Keywords: Navruz; navsard; Anno; Komoeditsa